Pengendalian Hama Lalat Buah Secara Terpadu Pada Lahan Pertanian Kelompok Tani Tunas Muda Arso 13 Skanto, Keerom - Supeni Sufaati; Daawia Daawia; Charisma Puspa Omega; Bambang Suhartawan (JURNAL PENGABDIAN PAPUA, 2026)
The integrated fruit fly pest control service was preceded by the fruit fly attack on the Tunas Muda Farmers Group's agricultural land. The Community Service activity was carried out for 3 weeks on the Tunas Muda Farmers Group's agricultural land in Arso 13, Skanto District, Keerom Regency. This community service activity was carried out using the extension method (FGD), Training in making fruit fly traps using Methyl Eugenol attractant, and Mentoring members of the Tunas Muda Farmers Group in implementing integrated fruit fly control on the Tunas Muda Group's agricultural land. Integrated fruit fly pest control was carried out with a variety of methods, namely mechanical fruit fly control or land sanitation, biologically with Methyl Eugenol attractant, and the use of botanical pesticides, fruit wrapping and refugia planting and fumigation. After the mentoring activity, it was continued with an evaluation of the effectiveness of integrated fruit fly control on reducing the fruit fly population on Tunas Muda agricultural land. The Community Service Activity was attended by 19 members of the Tunas Muda Farmers Group, Arso 13, Skanto District, Keerom Regency. The Community Service Activity was carried out in June 2025 with 3 Stages, namely Preparation, Activity Implementation and Evaluation. All stages went smoothly and the Farmers Group members were very enthusiastic about participating in all activities. Based on the evaluation results at the end of the community service activity, there was an increase in the knowledge and skills of the Tunas Muda group members in integrated fruit fly population control